2017
DOI: 10.20473/jvhs.v1.i2.2017.50-57
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Antecedent And Consequence Factors With Safety Behaviour In PT.X

Abstract: Background : Safety behaviour is an act worker to minimize the possibility of accidents in workplace. Based on the Antecedents-Behaviour-Consequence (ABC) theory, safety behaviour of worker related with the antecedent and consequence factors. Purpose : The purpose of this research was to study the association between antecedent and consequence factors with safety behaviour of workers in Ring Frame Unit Spinning II PT. X. Methods : This was an observational descriptive research with cross sectional approach. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The correlation between perception and safe behavior among workers can be seen through the correlation coefficient value of 0.799, which means that there is a strong correlation between perception and safe behavior among workers in the engineering and processing section PG Ngadiredjo Kediri, which means good perception will tend to behaving safely, but it is also possible that fair perception can also produce correct behavior. This result in line with previous research by Fitriani and Nawawiwetu (2017) that explains perceptions have a strong correlation with safe behavior among workers at PT Lotus Indah Textile with a contingency coefficient of 0.797. Based on that research, it can be concluded that workers who have a perception of danger and accidents in the workplace know that in their workplace there are dangers and know the accidents can be occur but are not comprehensive, this can produce fair safe behavior to avoid this as perceived…”
Section: The Correlation Between Perception and Safe Behavior Among E...supporting
confidence: 92%
See 1 more Smart Citation
“…The correlation between perception and safe behavior among workers can be seen through the correlation coefficient value of 0.799, which means that there is a strong correlation between perception and safe behavior among workers in the engineering and processing section PG Ngadiredjo Kediri, which means good perception will tend to behaving safely, but it is also possible that fair perception can also produce correct behavior. This result in line with previous research by Fitriani and Nawawiwetu (2017) that explains perceptions have a strong correlation with safe behavior among workers at PT Lotus Indah Textile with a contingency coefficient of 0.797. Based on that research, it can be concluded that workers who have a perception of danger and accidents in the workplace know that in their workplace there are dangers and know the accidents can be occur but are not comprehensive, this can produce fair safe behavior to avoid this as perceived…”
Section: The Correlation Between Perception and Safe Behavior Among E...supporting
confidence: 92%
“…This result in line with previous research by Fitriani and Nawawiwetu (2017) which explains that motivation has a strong correlation with safe behavior among workers at PT Lotus Indah Textile with contingency coefficient value of 0.622. Based on that research, in addition to motivating workers to behave safely, management must also provide facilities related to the formation of safe behavior, such as the availability of safety facilities.…”
Section: The Correlation Between Motivation and Safe Behavior Among E...supporting
confidence: 92%